Disturbances can facilitate prior invasions more than subsequent invasions in microbial communities - Luke Lear; Elze Hesse; Angus Buckling (Ecology Letters, 2024)
Invasions are commonly found to benefit from disturbance events. However, the importance of the relative timing of the invasion and disturbance for invader success and impact on community composition remains uncertain. Here, we experimentally test this by invading a five‐species bacterial community on eight separate occasions—four before a disturbance and four after. Invader success and impact on community composition was greatest when the invasion immediately followed the disturbance. However, the subsequent invasions had negligible success or impact. Pre‐disturbance, invader success and impact was greatest when the invader was added just before the disturbance. Importantly, however, the first three pre‐disturbance invasion events had significantly greater success than the last three post‐disturbance invasions. Moreover, these findings were consistent across a range of propagule pressures. Overall, we demonstrate that timing is highly important for both the success and impact on community composition of an invader, with both being lower as time since disturbance progresses.

Diversity loss from multiple interacting disturbances is regime‐dependent - Luke Lear; Hidetoshi Inamine; Katriona Shea; Angus Buckling (Ecology Letters, 2023)
Anthropogenic activities expose many ecosystems to multiple novel disturbances simultaneously. Despite this, how biodiversity responds to simultaneous disturbances remains unclear, with conflicting empirical results on their interactive effects. Here, we experimentally test how one disturbance (an invasive species) affects the diversity of a community over multiple levels of another disturbance regime (pulse mortality). Specifically, we invade stably coexisting bacterial communities under four different pulse frequencies, and compare their final resident diversity to uninvaded communities under the same pulse mortality regimes. Our experiment shows that the disturbances synergistically interact, such that the invader significantly reduces resident diversity at high pulse frequency, but not at low. This work therefore highlights the need to study simultaneous disturbance effects over multiple disturbance regimes as well as to carefully document unmanipulated disturbances, and may help explain the conflicting results seen in previous multiple‐disturbance work.

Disturbance‐mediated invasions are dependent on community resource abundance - Luke Lear; Daniel Padfield; Hidetoshi Inamine; Katriona Shea; Angus Buckling (Ecology, 2022)
Disturbances can facilitate biological invasions, with the associated increase in resource availability being a proposed cause. Here, we experimentally tested the interactive effects of disturbance regime (different frequencies of biomass removal at equal intensities) and resource abundance on invasion success using a factorial design containing five disturbance frequencies and three resource levels. We invaded populations of the bacterium Pseudomonas fluorescens with two ecologically different invader morphotypes: a fast‐growing “colonizer” type and a slower growing “competitor” type. As resident populations were altered by the treatments, we additionally tested their effect on invader success. Disturbance frequency and resource abundance interacted to affect the success of both invaders, but this interaction differed between the invader types. The success of the colonizer type was positively affected by disturbance under high resources but negatively under low. However, disturbance negatively affected the success of the competitor type under high resource abundance but not under low or medium. Resident population changes did not alter invader success beyond direct treatment effects. We therefore demonstrate that the same disturbance regime can either be beneficial or detrimental for an invader depending on both community resource abundance and its life history. These results may help to explain some of the inconsistencies found in the disturbance‐invasion literature.